2006
DOI: 10.1590/s0104-66322006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Semicontinuous cultivation of the cyanobacterium Spirulina platensis in a closed photobioreactor

Abstract: -The cultivation of photosynthetic microorganisms such as the cyanobacterium Spirulina platensis has been studied by researchers in many countries because these organisms can produce products with industrial potential. We studied the specific growth rate (µ x , day -1 ) and productivity (P x , in mg/L/day of Spirulina platensis biomass, dry weight basis) of two S. platensis strains (LEB-52 and Paracas) growing in aerated semicontinuous culture in two-liter Erlenmeyer flasks for 90 days (2160 h) at 30°C under 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 13 publications
2
43
1
7
Order By: Relevance
“…Since the cyanobacteria strains were reared at similar radiation conditions and in full nutrient medium, the negative growth rate results cannot be linked to non-adaptation towards the light regime, temperature or medium. In contrast, Moreno et al [63] observed production rates for D. lemmermannii (Tables A.1 and A.3), which is comparable to the studies of Reichert et al [79] with Spirulina cultures. Overall, in all treatments and on both Day 7 and Day 14, N. spumigena had statistically significantly higher biovolume and specific growth rate than both A. flos-aquae and D. lemmermannii, but not TFA per biovolume (Table A.1).…”
Section: Biovolume and Growthsupporting
confidence: 66%
“…Since the cyanobacteria strains were reared at similar radiation conditions and in full nutrient medium, the negative growth rate results cannot be linked to non-adaptation towards the light regime, temperature or medium. In contrast, Moreno et al [63] observed production rates for D. lemmermannii (Tables A.1 and A.3), which is comparable to the studies of Reichert et al [79] with Spirulina cultures. Overall, in all treatments and on both Day 7 and Day 14, N. spumigena had statistically significantly higher biovolume and specific growth rate than both A. flos-aquae and D. lemmermannii, but not TFA per biovolume (Table A.1).…”
Section: Biovolume and Growthsupporting
confidence: 66%
“…(Table II). The highest μ max value was 0.22 d Ð1 for strain LEB 18, which was higher than the 0.11 d Ð1 obtained for A. platensis in semi-continuous cultivation by Reichert et al (2006). Thus we found that the highest μ max value was obtained Table II.…”
Section: Resultsmentioning
confidence: 50%
“…Even when urea is used as a nitrogen source, ammonia is formed either by its hydrolysis under alkaline conditions (Danesi et al, 2002) or by urease activity (Shimamatsu, 2004). Spirulina platensis can be cultivated by batch, continuous, semicontinuous (Reichert et al, 2006) and fed-batch processes . The latter process, when conducted at both a suitable feeding time and feeding rate to supply the nitrogen source according to A. platensis demand, can avoid any inhibitory ammonia concentration in the medium (Bezerra et al, 2008;Carvalho et al, 2004;Matsudo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%